Multimodality imaging in patients with post-cardiac injury syndrome. Issue 9 (11th March 2020) - Verma, Beni R; Chetrit, Michael; Gentry III, James L; Noll, Andrew; Bafadel, Ahmed; Khayata, Mohamed; Harb, Serge C; Xu, Bo; Kontzias, Apostolos; Kwon, Deborah H; Jellis, Christine; Klein, Allan L
Abstract : This review article is focused on the role of echocardiography, cardiac CT and cardiac magnetic resonance (CMR) imaging in diagnosing and managing patients with post-cardiac injury syndrome (PCIS). Clinically, the spectrum of pericardial diseases under PCIS varies not only in form and severity of presentation but also in the timing varying from weeks to months, thus making it difficult to diagnose. Pericarditis developing after recent or remote myocardial infarction, cardiac surgery or ablation if left untreated or under-treated could worsen into complicated pericarditis which can lead to decreased quality of life and increased morbidity. Colchicine in combination with other anti-inflammatory agents (non-steroidal anti-inflammatory drugs) is proven to prevent and treat acute pericarditis as well as its relapses under various scenarios. Imaging modalities such as echocardiography, CT and CMR play a pivotal role in diagnosing PCIS especially in difficult cases or when clinical suspicion is low. Echocardiography is the tool of choice for emergent bedside evaluation for cardiac tamponade and to electively study the haemodynamics impact of constrictive pericarditis. CT can provide information on pericardial thickening, calcification, effusions and lead perforations. CMR can provide pericardial tissue characterisation, haemodynamics changes and guide long-term treatment course with anti-inflammatory agents. It is important to be familiar with the indications as well as findings from these multimodality imaging tools for clinical decision-making.